2003
DOI: 10.1902/jop.2003.74.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate Aminotransferase Activity in Gingival Crevicular Fluid During Orthodontic Treatment. A Controlled Short‐Term Longitudinal Study

Abstract: Our results suggest that AST levels in GCF reflect the biological activity which occurs in the periodontium during controlled occlusal trauma and, therefore, should be further evaluated as a diagnostic tool for monitoring correct orthodontic tooth movement in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 35 publications
1
68
0
1
Order By: Relevance
“…13,16,17 This method has been used especially for human studies, as it is a noninvasive method and repetitive sampling from the same side is possible. [3][4][5][6][7][8][9][10][13][14][15][16][17][18][19] Cytokines are local mediators released by cells of the immune system in response to stimulations, and orthodontic forces generate several cytokines that affect the formation and resorption of alveolar bone. 1,3,10,[13][14][15][16][17][18][19] Mechanical stress triggers the biological response of the periodontal ligament and plays an important role in remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,16,17 This method has been used especially for human studies, as it is a noninvasive method and repetitive sampling from the same side is possible. [3][4][5][6][7][8][9][10][13][14][15][16][17][18][19] Cytokines are local mediators released by cells of the immune system in response to stimulations, and orthodontic forces generate several cytokines that affect the formation and resorption of alveolar bone. 1,3,10,[13][14][15][16][17][18][19] Mechanical stress triggers the biological response of the periodontal ligament and plays an important role in remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…33 Thus, a lesser volume of GCF in the RDG may depend on reduced vascular supply because of the heavy force. On the other hand, Perinetti et al [4][5][6] suggested that inflammation rather than orthodontic tooth movement has an effect on the volume of GCF. In our study, initial PI, PD, and BOP were higher in the HRG, revealing more tendencies to gingival inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,68 Markers, such as OC, TGF-b, ALP, TNFa, CAB, epidermal growth factor, beta-2-microglobulin, glycosaminoglycans components, PGE2 as well as LDH activity and AST activity have been found to be significantly elevated in the GCF surrounding teeth undergoing orthodontic movement. 5,30,33,45,50,54,[68][69][70][71][72][73][74][75][76][77][78] The levels of interleukins in the GCF, especially those of IL-1b, IL-8, IL-2 and IL-6 have been shown to increase during orthodontic treatment. 72,[79][80][81][82] The GCF level of MMPs and their inhibitors has been generally shown to peak at an average of 1 to 2 days after the application of the stimulus and return to baseline values after approximately 1 week.…”
mentioning
confidence: 99%
“…GCF has been extensively studied as a source of sample [1,[6][7][8]. Inflammatory markers such as lactate dehydrogenase (LDH) [4] and aspartate aminotransferase (AST) [6,9] were studied. However, other inflammatory markers i.e.…”
Section: Introductionmentioning
confidence: 99%